HIV testing intentions and behaviors among 14-17-year-old sexual minority males. Issue 12 (2nd December 2019) - Norris, Alyssa L; Nelson, Kimberly M.; Carey, Michael P.
ABSTRACT: Adolescent sexual minority males have low rates of HIV testing despite increased risk for HIV acquisition. This study will examine adolescent sexual minority males' (a) HIV testing behaviors and intentions, and (b) associations with disclosure to healthcare providers of male-male attraction. Sexual minority males were recruited using social media sites to obtain a national sample. Participants ( N  = 207) were 14-17-year-old cisgender males living in the U.S. who (1) self-identified as gay/bisexual, (2) reported sexual attraction to males, or (3) reported past-year voluntary sexual contact with a male. Only 14% of participants reported they had tested for HIV, even though 20% reported a history of condomless anal intercourse with male partners. Three-quarters (77%) planned to test for HIV, but only 48% planned to test annually (i.e., current CDC recommendation). Only 20% of participants had disclosed male-male attraction to their healthcare provider, but adolescents who disclosed had five times the odds of testing for HIV (AOR = 5.40). Rates of HIV testing and disclosure of male-male interests to a healthcare provider are low among adolescent sexual minority males. Given the association between disclosure and HIV testing, creating non-judgmental healthcare settings and optimizing patient-provider communication are likely to improve uptake of HIV testing by at-risk youth.